Diagnostic strategies for differentiating Crohn’s disease from intestinal tuberculosis: a systematic review of clinical, endoscopic, radiological, histopathological and microbiological features - Aysha Hussein; Doaa Aljanabi; Goud Alassaf; Lana Sabouni; Lujain Alkasir; Rama Rabboua; Yasmeen Mostafa; Wael Hassan (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background Crohn’s disease (CD) and intestinal tuberculosis (ITB) share many clinical, endoscopic, radiologic, and histopathologic features, making accurate differentiation difficult and increasing the risk of inappropriate management. Aim To compare the key features of CD and ITB and identify findings that may support differential diagnosis. Methods A PRISMA 2020-guided systematic review was conducted and registered in PROSPERO (CRD420251137667). PubMed and Scopus were searched for English-language studies published between 1 January 2020 and 31 December 2025, with supplementary searches of Google Scholar, BioMed Central, and The Lancet publisher platforms. Risk of bias and applicability were assessed independently by two reviewers using QUADAS-2, with disagreements resolved by consensus. Results Nineteen studies were included in the narrative synthesis. Perianal disease, gastrointestinal bleeding, longitudinal ulcers, skip lesions, cobblestoning, asymmetrical mural thickening, and the comb sign favored CD; ascites, pulmonary tuberculosis, transverse or annular ulcers, continuous ileocecal involvement, short concentric strictures, and necrotic mesenteric lymph nodes favored ITB. High risk of bias was most frequent for patient selection (16/19; 84.2%), flow and timing (13/19; 68.4%), and the reference standard (11/19; 57.9%); 17/19 studies (89.5%) were at high overall risk. Conclusion No single feature reliably distinguishes CD from ITB. Diagnosis should use a multidisciplinary, multimodal approach, and reported performance estimates should be interpreted cautiously because of substantial methodological limitations.